Membangun Kefahaman : Landasan Epistemlogi Kefilsafatan dalam Islam - Nurhikmah; Santalia, Indo; Syamsuddin (CV Kalimasada Group, 2023)
Philosophical epistemology in Islam has always been an interesting subject for researchers to study. This topic is one of the most frequently debated and discussed in the field of philosophy, for example about what knowledge is, what its characteristics are, types, and its relationship to truth and belief. The objective framework above is used to gain or obtain this knowledge so that it is not an exaggeration to assume that the epistemological conception is an idealistic epistemological system that differentiates it from other thinkers, both contemporaries and other later (modern) thinkers. This research seeks to analyze and describe the epistemological basis of Islamic philosophy. In accordance with the characteristics of the problem raised in this research, qualitative research methods are used, namely emphasizing the analysis on descriptive data in the form of observed written words. The author uses a qualitative approach to analyze the study of the Epistemological Foundations of Philosophy in Islam. The method used in this study uses a library research method or approach. The research results in this study found that Islamic philosophical epistemology recognizes the existence of the senses, reason and intuition. Muslim scientists have a strong belief in the ontological status of not only visible physical objects, but also unseen metaphysical objects. Even though metaphysical objects cannot be seen by the senses, they are believed to have an ontological status that is as real as physical objects, even more real than sense objects. Therefore, there is a difference of opinion with western philosophy which only relies on ratios.